2023
DOI: 10.55860/bcuq4622
|View full text |Cite
|
Sign up to set email alerts
|

Doping prevalence and attitudes towards doping in Dutch elite sports

Abstract: The use of performance enhancing substances among elite athletes is a well-known phenomenon, but data on prevalence are inconsistent. The aim of this study was to investigate (1) the prevalence of doping use in Dutch elite athletes and (2) the attitude of elite athletes with regard to the use of performance enhancing substances. A total of 272 elite athletes completed an online questionnaire about doping use using the randomised response method and about their attitude towards the use of performance enhancing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Data from an unpublished manuscript [30], shared with permission to include, were presented in a conference abstract [31] in English. Additionally, results from the more recent doping prevalence study in the Netherlands [32,33] were published in Balk et al [34]. Studies by Ulrich et al [35] and Petróczi et al [36] were conducted in the same settings (and with the same sample for one set of data) but using different IEM, whereas Ulrich et al [37] presents a reanalysis of the data reported in Petróczi et al [36].…”
Section: Overview Of Outputsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from an unpublished manuscript [30], shared with permission to include, were presented in a conference abstract [31] in English. Additionally, results from the more recent doping prevalence study in the Netherlands [32,33] were published in Balk et al [34]. Studies by Ulrich et al [35] and Petróczi et al [36] were conducted in the same settings (and with the same sample for one set of data) but using different IEM, whereas Ulrich et al [37] presents a reanalysis of the data reported in Petróczi et al [36].…”
Section: Overview Of Outputsmentioning
confidence: 99%
“…The 33 studies included in the meta-analysis sampled 43121 (speci ed n: males = 13508, females = 2725) participants. Sample size ranged from 249 [34] to 4629 [13] with a mean of 1347.53 (SD = 1083. 19) and were justi ed by power analysis in six studies [40,42,[44][45][46][47].…”
Section: Participantsmentioning
confidence: 99%
“…Moreover, in a further recent publication [ 6 ] which included Drs. Cruyff and de Hon as co-authors, it is stated:…”
Section: Introductionmentioning
confidence: 99%